(untitled) (Research, Society and Development, 2024)
Brazil stands out as the leading global producer and consumer of yellow passion fruit, with an estimated production of about 700,000 tons in 2023. Passion fruit cultivation generally takes place on small farms, many with orchards ranging between 3 and 5 hectares. Despite challenges such as high susceptibility to diseases, passion fruit farming has been attractive due to its significant economic value, which is essential to meet the quality standards of consumer markets. Therefore, the aim of this research was to assess the incidence of diseases in passion fruit plants in an experimental area of the Federal Institute of Triângulo Mineiro - Uberlândia campus, MG. The varieties of passion fruit used were FB300, FB200, Gigante Amarelo, Mel do Cerrado, Sertão Forte, and Pérola do Cerrado. These varieties were planted in December 2022, with 8 rows of 14 plants and a spacing of 3 x 3 meters. Disease assessments were carried out biweekly from March to July 2023, totaling 4 evaluations. The experimental design used was randomized blocks, with 6 varieties and 4 replications, totaling 24 experimental plots. The diseases evaluated were: anthracnose, angular leaf spot, bacterial spot, viral diseases, and scab. The varieties showed differences only in relation to anthracnose, with the varieties Mel do Cerrado, Sertão Forte, and Pérola do Cerrado showing lower disease incidence, demonstrating greater resistance to this pathogen. For the other diseases evaluated, the varieties did not differ statistically.